Diseño de un manual de buenas prácticas de manufactura para la microempresa de lácteos “La Victoria” de la provincia de Cotopaxi - Díaz Casa, Paola Andrea (2019)
The demands of the markets and the awareness of consumers to obtain healthy food, force companies to comply with quality and safety standards for their products, subjecting themselves to the (BPM) Good Manufacturing Practices where they comply with the necessary requirements to obtain quality products and provide consumer safety. Currently the company "LA VICTORIA" does not have a Manual of Good Manufacturing Practices, which represents a weakness for it, reducing the degree of competitiveness compared to others, dedicated to the development of similar products. After evaluating their current situation, the following result was obtained: that 43.3% comply with the provisions of the official record No. 555 of executive decree 662 of the year 2015 and 56.7% do not comply, so taking these percentages into account, we proceeded to develop the BPM manual that will reduce the contamination present in production, thus allowing its recognition at the national level.